PROSES PEMEROLEHAN BAHASA ANAK - Muzaiyanah Muzaiyanah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
Language and communication disorders can be caused by medical factors and environmental factors. Medical factors implicated in disorders of speech, language disorders and impaired thinking. The examples of medical factors that disruption as a result of a brain injury that causes damage to the nervous system, psychogenic disorders, and disorders of the organ mechanism speech system. Similarly, damage to the nervous system that causes a network disconnection between the production area of auditory and speech said that the message was not delivered. In general, there are two opinions regarding second language acquisition. First, children are born already familiarized exposed to various languages. Secondly, children learn a second language as their mother tongue can be pronounced properly. These two arguments are just as good, but nevertheless still have drawbacks. The first method can result in the emergence of speech delay due to a child's brain is working hard to map the language that is spoken by people who asked children to speak. But this does not last longer, when children are growing, their abilities will be honed by themselves. The second method results in the pronunciation of the second language would be worse than a child with the first method. Children in the first method will be familiar with the pronunciation and accent clearer. However, both of these methods can be used, by paying attention the condition of language acquisition that are interactive, motivating and attractive.